Works by women Artists from the Logan Collection. - Ross, David A.; Salvioni, Daniela (San Francisco : San Francisco Museum of Modern Art, 1999)
Ackermann, Rita ; Adelman, Shonagh ; Antoni, Janine ; Dingle, Kim ; Floyer, Ceal ; Fritsch, Katharina ; Holzer, Jenny ; Lockhart, Sharon ; Noland, Cady ; Porges, Maria ; Post, Liza May ; Ruyter, Lisa ; Sherman, Cindy ; Simmons, Laurie ; Smith, Kiki ; Stewart, Kerry ; Taylor-Wood, Sam ; Tyson, Nicola ; Williams, Sue ; Yuskavage, Lisa
Works by women Artists from the Logan Collection, San Francisco Museum of Modern Art, San Francisco, January 9 to April 20, 1999
Engels
boek